Propofol versus midazolam for sedation during radiofrequency ablation in patients with hepatocellular carcinoma. Issue 2 (22nd December 2020) - Kanogawa, Naoya; Ogasawara, Sadahisa; Ooka, Yoshihiko; Inoue, Masanori; Wakamatsu, Toru; Yokoyama, Masayuki; Maruta, Susumu; Unozawa, Hidemi; Iwanaga, Terunao; Sakuma, Takafumi; Fujita, Naoto; Koroki, Keisuke; et al.
Abstract: Background and Aim: Standardization of the sedation protocol during radiofrequency ablation (RFA) in patients with hepatocellular carcinoma (HCC) is needed. This randomized, single‐blind, investigator‐initiated trial compared clinical outcomes during and after RFA using propofol and midazolam, respectively, in patients with HCC. Methods: Few‐ and small‐nodule HCC patients (≤3 nodules and ≤3 cm) were randomly assigned to either propofol or midazolam. Patient satisfaction was assessed using a 100‐mm visual analog scale (VAS) (1 mm = not at all satisfied, 100 mm = completely satisfied). Sedation recovery rates 1, 2, 3, and 4 h after RFA were evaluated based on Modified Observer's Assessment of Alertness/Sedation (MOAA/S) scores; full recovery was defined as a MOAA/S score of 5. Results: Between July 2013 and September 2017, 143 patients with HCC were enrolled, and 135 patients were randomly assigned to the treatment group. Compared with midazolam, propofol exhibited similar median procedural satisfaction (propofol: 73.1 mm, midazolam: 76.9 mm, P = 0.574). Recovery rates 1 and 2 h after RFA were higher in the propofol group than in the midazolam group. Meanwhile, recovery rates observed 3 and 4 h after RFA were similar in the two groups. The safety profiles during and after RFA were almost identical in the two groups. Conclusion: Patient satisfaction was almost identical in patients receiving propofol and midazolam sedation during RFA. Propofol sedation resulted in reduced recovery time compared with midazolam sedation in patients with HCC. The safety profiles of both propofol and midazolam sedation during and after RFA were acceptable. Abstract : The standardization of sedation protocol during radiofrequency ablation (RFA) in patients with hepatocellular carcinoma (HCC) is needed. This randomized, single‐blind, investigator‐initiated trial compared clinical outcomes during and after RFA using propofol and midazolam, respectively, in patients with HCC.